Hybrid argon plasma coagulation-assisted endoscopic mucosal resection for large sessile colon polyps to reduce local recurrence: a prospective pilot study - Motz, Victoria L.; Lester, Courtney; Moyer, Matthew T.; Maranki, Jennifer L.; Levenick, John M. (Endoscopy, 2021)
Background Endoscopic mucosal resection (EMR) of large, sessile colon polyps often results in incomplete resection with subsequent recurrence. The aim of this prospective pilot study was to evaluate the efficacy and safety of a novel technique, hybrid argon plasma coagulation-assisted EMR (hAPC-EMR), to remove large, sessile polyps.Methods 40 eligible patients underwent hAPC-EMR for the removal of one or more nonpedunculated colon polyps ≥ 20 mm. Participants were contacted 30 days post-procedure to assess for adverse events and were recommended to return for a surveillance colonoscopy at 6 months to assess for local recurrence.Results At the time writing, 32 patients with 35 polyps (median size 27 mm; interquartile range 14.5 mm) resected by hAPC-EMR had undergone the 6-month follow-up colonoscopy. Recurrence rate was 0 % (95 % confidence interval [CI] 0–0) at follow-up. Post-polypectomy bleeding was experienced by three patients (7.5 %; 95 %CI 0.00–0.15), and no patients developed post-polypectomy syndrome.Conclusion These preliminary results showed 0 % local recurrence rate at 6 months and demonstrated the safety profile of hAPC-EMR. A large, randomized, controlled trial is required to confirm these results.